Tribological and Corrosion Analysis of TiO2 and C–Based HVOF-Sprayed Hybrid Composite Coatings - Bhuwan Khare; null Yashpal; Ratnesh Kumar Sharma (Advances in Materials Science and Engineering)
Currently, there is a significant need for affordable coatings that are both authentic and ecofriendly, with the goal of reducing pollution. In order to mitigate frictional loss, researchers have produced hybrid coating based on carbon through the utilization of the high-velocity oxygen fuel (HVOF) spray technique. The results showed that the coefficients of friction (COFs) varied in the range of 0.1–0.5, and the wear rates ranged from 40 to 115 μm. The experiments were performed under different situations, encompassing temperatures ranging from 50°C to 200°C, loads ranging from 40 to 55 N, and sliding speeds ranging from 0.3 to 1.2 m/s. The corrosion tests showed a decrease in mass loss from 0.15 to 0.02 g after 1 h of immersion and from 0.20 to 0.04 g after 5 h of immersion. The tribological testing revealed significant improvements in various properties. The microhardness increased by 78.7%, residual stress decreased by 78%, mass loss due to corrosion decreased by 60% after 1 h and 62.5% after 5 h, coefficient of friction decreased by 76.9%, and wear rate reduced by 62.5%.